2006
DOI: 10.1677/jme.1.01971
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrochemistry of human, bovine and porcine cytochrome P450c17

Abstract: The direct electrochemistry of human, bovine and porcine cytochrome P450c17 (CYP17) has been examined on an edge-oriented pyrolytic graphite electrode. The recombinant protein was immobilized on an electrode modified with a surfactant to simulate the environment of a biological membrane, and hence physiological electron-transfer conditions. The P450 enzymes all retained 'electron-transfer' activity while immobilized at the electrode surface as assessed by the presence of catalytic signals under aerobic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 71 publications
0
11
0
1
Order By: Relevance
“…Thus, liganding to the recombinant human enzyme of pregnenolone and progesterone together with their respective 17 -hydroxy derivatives displayed K d values ranging from 1.4 to 5.3 μM accompanied by a considerable yield in high-spin conversion of the hemoprotein [175]. Even so, direct electrochemistry of the P450 from human, bovine and porcine sources immobilized on an edge-oriented pyrolytic graphite electrode failed to demonstrate any effect of these substrates/metabolic intermediates on the midpoint potential of CYP17 [176]. Moreover, turnover numbers were moderate [175], with the ratio of 17 -hydroxylase to C 17 -C 20 desmolase activity being modulated by the presence of b 5 [177].…”
Section: The Cyp11 and Cyp17 Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, liganding to the recombinant human enzyme of pregnenolone and progesterone together with their respective 17 -hydroxy derivatives displayed K d values ranging from 1.4 to 5.3 μM accompanied by a considerable yield in high-spin conversion of the hemoprotein [175]. Even so, direct electrochemistry of the P450 from human, bovine and porcine sources immobilized on an edge-oriented pyrolytic graphite electrode failed to demonstrate any effect of these substrates/metabolic intermediates on the midpoint potential of CYP17 [176]. Moreover, turnover numbers were moderate [175], with the ratio of 17 -hydroxylase to C 17 -C 20 desmolase activity being modulated by the presence of b 5 [177].…”
Section: The Cyp11 and Cyp17 Enzymesmentioning
confidence: 99%
“…Also, the V max /K m value for deoxycorticosterone conversion to aldosterone is about 47% that found for transformation of the steroid to corticosterone [174], negating the possibility of the rate-limiting steps in the two metabolic branches to be identical. Furthermore, steroid-induced changes in the redox properties of CYP17 are obviously not required to support hydroxylase/lyase activity in hormone synthesis [176].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canis familiaris is one of the most widely studied animal models used in safety determination of new pharmaceuticals [11][12] and, although the major isoforms of the human cytochromes P450 2D6, 3A4, 2E1, 2C19 and 1A2 have been identified in C. familiaris [13][14][15][16], there is still a lack of knowledge on their pharmacogenomic/metabolic diversity [9]. Electrochemical techniques already developed in our lab for human hepatic monooxygenases including cytochromes P450 [17][18][19][20][21][22] represent the ideal approach for a sensitive, accurate and rapid evaluation of animal P450-drug interactions obviating both the requirement for a redox partner and the addition of NADPH cofactor as already reported for some animal P450 enzymes recombinantly expressed in a soluble form [23][24][25]. In this work, Canis familiaris P450 2D15 was chosen as a model for the investigation of canine cytochromes P450 by adopting electrochemical approaches to provide a method for the screening of the safety of new chemical entities/drugs.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great interest that P450c17 from different species appear to have different enzymatic activities (Buczko et al, 1995;Chung et al, 1987;Conley et al, 1992;Conley and Bird, 1997;Fevold et al, 1989;Lin et al, 1994;Namiki et al, 1988;Ono et al, 1988;Picodo-Leonard and Miller, 1987;Provencher et al, 1992;Simpson et al, 1987;Swart et al, 1993;Tremblay et al, 1994;Zuber et al, 1986). The factors that regulate these different activities of the P450c17 and the possible relationship of these differences to the protein structure that may differentiate enzymatic activities have been the topic of numerous investigations (Arlt et al, 2002;Brock and Waterman, 1999;Gilep et al, 2003;Gilep et al, 2004;Johnson et al, 2006;Lee-Robichaud et al, 1997;Lewis et al, 1998;Mathieu et al, 2000). In addition, cytochrome b 5 (b 5 ) has been identified as an important modulator of C17,20-lyase activity of porcine P450c17 enzyme (Katagiri et al, 1982;Onoda and Hall, 1982) and this has since been confirmed in reconstitution experiments in several laboratories with various P450c17 enzymes (Auchus et al, 1998;Brock and Waterman, 1999;Katagiri et al, 1995;Lee-Robichaudet et al, 1995Miller and Auchus, 2000).…”
Section: Introductionmentioning
confidence: 99%